Do solar green roofs contribute to SDGs, fostering energy efficiency and environmental conservation? - Mohanad M. Ibrahim; Micheal A. William; Aly M. Elharidi; Ahmed A. Hanafy; María Jose Suarez-Lopez (Renewable Energy and Sustainable Development, 2024)
The study investigates the energy efficiency of buildings by analyzing the collective advantages of numerous roof enhancement techniques, such as green roofs, solar gardens technologies, reflective paint coatings, and thermal insulation, in different climate regions. This emphasizes the significance of considering regional variances and meteorological factors when adopting energy-efficient building solutions, providing tailored recommendations that can be adjusted to specific geographical conditions. The research uses a rigorous technique to assess these roof improvements in four locations, uncovering substantial energy savings. For instance, when green roofs and solar technology are used together, there is an average reduction of 40%. Similarly, applying reflective paint results in an average decrease of 12.96%. On the other hand, thermal insulation provides the lowest percentage of savings, with an average of 2.65% across various locales. Based on economic analysis, reflective paint is the most cost-effective option, with reduction cost per kilowatt-hour from $0.12 to $0.17. However, green roofs and solar gardens have proven economically viable since they have considerable reduction cost per kilowatt-hour, ranging from $3.53 to $2.16. The study highlights the significance of customized strategies to optimize energy efficiency outcomes, offering essential knowledge for urban planners and policymakers. Applying these findings ensures a quantifiable decrease in energy use and establishes the foundation for sustainable and eco-friendly cities for future generations.   Received: 10 July 2024 Accepted: 23 August 2024 Published: 23 September 2024